Public and Healthcare Professional Perceptions of Clinical Nurse Specialists: A Scoping Review - Eny Dewi Pamungkas; Mustaqimah; Raphita Diorarta; Hesti Rahayu; T. Widya Naralia; Syamikar Baridwan Syamsir (Fakultas Keperawatan Universitas Andalas, 2026)
Clinical Nurse Specialists (CNSs) play a critical role in advanced nursing practice, however, their professional identity and public recognition remain inconsistent across healthcare systems. This study aims to explore how both the public and healthcare professionals perceive the role of CNSs, with attention to perceived competencies, contributions, and challenges. A scoping review was conducted using Arksey and O’Malley’s (2005) framework and reported according to PRISMA-ScR guidelines. Searches were performed in Scopus, PubMed, Wiley, and ProQuest for studies published between 2015 and 2025 using keywords related to CNS roles and perceptions. The screening and selection process was conducted by two independent reviewers. Data from the included studies were analyzed using narrative and thematic approaches. From 1,245 records, five studies met the inclusion criteria. Both the public and healthcare professionals viewed CNSs as highly skilled clinicians with strong leadership, empathetic communication, and key roles in interprofessional coordination and patient empowerment. Challenges included limited public understanding, role overlap with general nurses, and insufficient regulatory support. While perceptions of CNSs are generally positive, greater regulatory clarity, enhanced advanced nursing education, and improved communication strategies are needed to strengthen recognition and effectiveness of CNS roles in healthcare systems.